Effect of Water Adsorption on Bilayer h-BN: First-Principles Study - Paudel, G.; Nepal, M.; Aryal, S.; Devkota, A.; Neupane, H. K. (Journal of Nepal Physical Society, 2023)
Recent years have seen a great deal of excitement in the study of the structural, electronic and magnetic behavior of two-dimensional (2D) materials. This has great promise for improved electronics, fascinating quantum technologies, and energy-efficient gadgets. In the current work, we have investigated the structural, electronic, and magnetic properties of bilayer h-BN and water adsorption on pristine h-BN bilayer supercell material using the density functional theory (DFT) method. We have examined the structural properties, and found that they are structurally stable materials. We have examined the band structure and density of states (DoS) calculations of h-BN, and water adsorbed h-BN materials. It is found that water adsorbed on pure h-BN is an n-type Schottky semiconducting material, and pristine h-BN is a broad bandgap p-type Schottky material. P-type insulating material becomes n-type semiconducting material when water molecules are adsorbed. Additionally, after looking the materials' magnetic properties through their DoS and partial density of states (PDoS) analysis. We found that h-BN, and water adsorbed h-BN have non-magnetic properties. Thus, they have been employed extensively in many different industries because of their bandgap energy and non-magnetic in nature.